Questioning editors who blame COVID-19 for their editorial failures - Jaime A. Teixeira da Silva (National Scientific Medical Center, 2024)
The Covid-19 pandemic has provided an opportunity to appreciate how delays in medical treatments can negatively impact the healthcare of patients in need. However, not much - if anything - has been researched on how the pandemic has been used as an excuse within professional settings. In this letter, I take note of a personal case in which an editor of a ranked and indexed medical journal, having taken four months to issue a desk rejection, promptly blamed Covid-19 for the journal's editorial failures, without providing proof of this claim. Currently, editors who issue such statements cannot be held accountable, and the system of publication needs to change in order to prevent editors from making such ludicrous claims without publicly verifiable evidence. Absent concrete measures to safe-guard authors' rights to know why their papers' intellect has been held up for so long, they become victims of a system that offers unprecedented unchecked powers to editors.